Effect of crack width on residual strength of RC beam after crack treatment / Augustine Kudi - Kudi, Augustine (1998)
Crack width on the surface of the beam, is an essential factor as so to meet the serviceability requirement based on the code of practice. Crack on the surface of the beam definitely leads to the corrosion of reinforcement bar, in other words, it reduces the member capability to withstand any environmental changes and high loading. Therefore the best we can do now is to control the crack width on the surface of the member. An adequate value of crack width ha s been fixed in the BS 8110: Part 2 an approximately 0.1-0.2mm. In treating cracks, one alternative is to use epoxy resin, to fill the cavities, and hence to control the residual strength of concrete. There are various types of éribxy resin in the markèt. Some of them such as Sikadur 752 and expofill. Expofill was chósen herë since it is the most common bonding agent available in our rriarket. In this study, the treatment of crack via injection Öf epoxy resih nas proved to make it possible to restore the residual strength of the srructural beam.